Antioxidant Activity of DLω-Phenyl-Amino Acid Octyl Esters with Anti-inflammatory Activity - Kontogiorgis, Christos A.; Hadjipavlou-Litina, Dimitra J.; Schulz, Elisabeth (Arzneimittelforschung, 2001)
The antioxidant activities (in vitro) and the lipophilicity (as RM values) of 12 DL-ω-phenyl-amino acid octyl esters with anti-inflammatory/analgesic activities were studied. The tested compounds were found to interact with 1,1-diphenyl-2-picrylhydrazyl stable free radical (DPPH), whereas most of them were essentially inactive in other tests. DL-2-Amino-4-(4-aminophenyl)butyric acid octyl ester was found to be the most active. The anti-inflammatory activity does not seem to be connected with O2− or HO. scavenging activity at least under the experimental conditions applied. However, the interaction with DPPH was found to be correlated with their anti-inflammatory activity. Between the lipophilicity and the anti-inflammatory activity only a poor relationship exists. For a subgroup of the derivatives of the phenyl glycine octyl ester (1–8) a significant correlation was found between the RM values and the calculated clog Ρ lipophilicity.
Keywords: Anti-inflammatories; Phenyl-amino acid esters, antioxidant activity, in vitro studies; Radicals